2017
DOI: 10.18632/oncotarget.21602
|View full text |Cite
|
Sign up to set email alerts
|

Predictive clinical parameters for the response of nivolumab in pretreated advanced non-small-cell lung cancer

Abstract: BackgroundNivolumab offers a superior survival benefit over docetaxel in patients with advanced, previously treated non-small-cell lung cancer (NSCLC). An association between programmed cell death ligand-1 (PD-L1) expression and the efficacy of nivolumab has been reported in many studies. However, the association between the clinical parameters and efficacy of nivolumab remains unclear in advanced NSCLC patients.ResultsAmong 124 patients, 108 (88%) were performance status (PS) 0 to 1. PD-L1 expression was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
94
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 56 publications
(58 reference statements)
10
94
6
Order By: Relevance
“…As we all known, CRP is a strong prognostic predictor in many cancers. As reported previously 14,33 , patients without elevation of pretreatment CRP level have better prognosis than those with elevated pretreatment CRP level. Wilop et al found that normalization of CRP during chemotherapy was associated with better prognosis 15 .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…As we all known, CRP is a strong prognostic predictor in many cancers. As reported previously 14,33 , patients without elevation of pretreatment CRP level have better prognosis than those with elevated pretreatment CRP level. Wilop et al found that normalization of CRP during chemotherapy was associated with better prognosis 15 .…”
Section: Discussionsupporting
confidence: 65%
“…It's also found that a high circulating CRP level in lung cancer patients also indicated shorter survival 12,13 . A study on advanced cancer patients revealed that baseline CRP was an independent prognostic factor for survival in patients with advanced NSCLC receiving palliative rst-line chemotherapy 14 . Another available evidence shows that measurement of CRP both before initiation and during a platinum-based chemotherapy may provide prognostic information for the individual patient with advanced NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports, including our report, that ICI treatment has less efficacy in patients with poor PS or high CRP. It is thought that these are due to immunosuppression and the relationship with inflammatory cytokines [31][32][33], but the reasons are not clear. Therefore, CRP is not a clear biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…However, retrospective data support a relationship between LDH levels and clinical outcome following immunotherapy in other tumor types (Table 1). [6][7][8][9][10][11] In this review, we describe mechanisms that may result in elevated LDH levels in cancer patients. Elevated LDH levels are the product of enhanced glycolytic activity of the tumor and tumor necrosis due to hypoxia, the latter being associated with high tumor burden.…”
Section: Introductionmentioning
confidence: 99%